Multiobjective constrained optimal synthesis of planar mechanisms using a new evolutionary algorithm - Cabrera-Carrillo, Juan Antonio; Nadal-Martínez, Fernando; Muñoz, J. P.; Simón-Mata, Antonio (Elsevier, 2007)
The paper deals with solution methods to multiobjective optimization problems. A searching procedure is developed, which applies genetic algorithms based on evolutionary techniques. The new method has proved to solve synthesis problems of planar mechanisms and has been used for testing a hand robot mechanism, showing that the solutions are accurate and valid for all cases. The extension of the method to other mechanism types has been outlined. The main advantages of the method are its simplicity of implementation and its fast convergence to optimal solutions, with no need of extensive knowledge of the searching space.
Keywords: Algoritmos genéticos; Mechanism synthesis; Genetic algorithms; Multiobjective optimization; Evolutionary techniques